2015
DOI: 10.3390/toxins7114817
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Profiles of Ricin-Cell Interactions in the Lung Following Intranasal Exposure to Ricin

Abstract: Ricin, a plant-derived exotoxin, inhibits protein synthesis by ribosomal inactivation. Due to its wide availability and ease of preparation, ricin is considered a biothreat, foremost by respiratory exposure. We examined the in vivo interactions between ricin and cells of the lungs in mice intranasally exposed to the toxin and revealed multi-phasic cell-type-dependent binding profiles. While macrophages (MΦs) and dendritic cells (DCs) displayed biphasic binding to ricin, monophasic binding patterns were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 35 publications
3
54
1
Order By: Relevance
“…Early neutrophil accumulation has been observed in the lung tissue of ARDS patients (14), and a poor prognosis in septic ARDS was found to correlate with elevated neutrophil counts in BALF 39). Rapid and high level recruitment of neutrophils to the lungs has been well documented in pulmonary ricinosis animal models (7,20,30,33,35). Since the administration of anti-ricin Ab treatment at 24 h postexposure to ricin resulted in significantly reduced levels of pulmonary EBD (see Fig.…”
Section: Total Body Irradiation Mitigates Pulmonary Edema Formation Amentioning
confidence: 89%
See 1 more Smart Citation
“…Early neutrophil accumulation has been observed in the lung tissue of ARDS patients (14), and a poor prognosis in septic ARDS was found to correlate with elevated neutrophil counts in BALF 39). Rapid and high level recruitment of neutrophils to the lungs has been well documented in pulmonary ricinosis animal models (7,20,30,33,35). Since the administration of anti-ricin Ab treatment at 24 h postexposure to ricin resulted in significantly reduced levels of pulmonary EBD (see Fig.…”
Section: Total Body Irradiation Mitigates Pulmonary Edema Formation Amentioning
confidence: 89%
“…In pulmonary ricinosis, the toxin enzymatically inactivates ribosomes by a unique 28S rRNA ribosomal depurination mechanism, thereby inducing death of inflammatory cells, dendritic cells, macrophages, lung parenchymal cells, blood endothelial cells, and alveolar epithelial cells (35). At the clinical level, pulmonary exposure to ricin induces neutrophil influx to the lungs accompanied by a cytokine storm and the generation of a severe edema in the alveoli and pulmonary interstitium, which in turn leads to respiratory failure and death (11,35,44). Recently, we have shown that the clinical manifestations of ricin-induced respiratory damage in swine comply fully with the accepted diagnostic criteria for ARDS (18).…”
Section: Introductionmentioning
confidence: 99%
“…Although this mode of exposure may not accurately replicate inhalatory exposures, we have demonstrated in the past that intranasal exposure of mice to ricin, brings about extensive pulmonary damage, including the generation of an acute edematous lung inflammation and damage of lung cell subtypes (Gal et al, 2014;Sapoznikov et al, 2015). Ribosome depurination quantitation was accomplished by developing a method for measuring depurination levels, utilizing a primary extension assay previously described (Iordanov et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Toxins were prepared as previously described (Gal et al, 2014;Sapoznikov et al, 2015;Sabo et al, 2015). Briefly, seeds of Ricinus communis or Abrus precatorius were homogenized in a Waring blender in 5% acetic acid/phosphate buffer (Na2 HPO4, pH 7.4) the homogenate was centrifuged and the clarified supernatant containing the toxin was subjected to ammonium sulphate precipitation (60% and 80% saturation, for ricin and abrin, respectively).…”
Section: Ricin and Abrin Preparationmentioning
confidence: 99%
“…Crude ricin was prepared from seeds of endemic Ricinus communis, essentially as described before [9]. Briefly, seeds were homogenized in a Waring blender in 5% acetic acid/phosphate buffer (Na 2 HPO 4 , pH-7.4), the homogenate was centrifuged and the clarified supernatant containing the toxin was subjected to ammonium sulfate precipitation (60% saturation).…”
Section: Extraction and Purification Of Abrin And Ricinmentioning
confidence: 99%